Impact of inflation on sports consumption: A study on fitness facilities - Balatoni, Ildikó; Gambo, Adamu Umar (Tér - Gazdaság - Ember/Journal of Region, Economy and Society, 2023)
Fitness centers, as micro and small enterprises, are important to the economic development of a country and the health of its citizens. However, the small size of most fitness centers makes their existence precarious. This study aims to assess the impact of inflation on fitness centers. The researchers chose Debrecen, a community in Hungary with a considerable fitness sector,as the center of their investigation. Telephone interviews using structured questionnaires were conducted among all twenty fitness centers operating in Debrecen. Answers were analyzed using descriptive statistical methods. Most respondents indicated that the price of their services had increased due to energy costs. One-third believed these increases negatively affected members’physical activity (PA). In contrast, two-thirds indicated that customers were willing to accept the price increase. Despite rising costs, workforce reductions seldom occurred. Instead, fitness centers were modernized to maintain attendance and reduce energy costs, and became increasingly active online, mainly through social media. It is concluded that price increases did not significantly affect physical activity participation.